Prevalence Rate and Infection Degree of Helminthiasis on Pigeon (Columbia Livia Domestica) in North Surabaya - Ihda Hanny, Khurun'In Fadia; Djoko Legowo; Mufasirin; Kusnoto; Dian Ayu Permatasari; Poedji Hastutiek (Journal of Parasite Science, 2023)
Pigeon meat is an alternative option to other poultry meat such as chikens. As pigeons are easy to keep and quickly reproduce. Improper hygene practices is a strong factor in helminthiasis transmission. This study aims to know the prevalence and degree of infection of helminthiasis in North Surabaya. 70 samples were taken from pigeon butchers in North Surabaya from September to November 2022. Dissection method was used for prevalence rate count and modified McMaster method was used to count degree of infection. The result shown that 70% of samples had positive worm infection. Types of worms found were R. cesticillus (55.7%), Ascaridia sp. (25.7%), Capillaria sp. (14.2%), Echinostoma sp. (2.8%) and Heterakis sp. (1.4%). Qualitative exam shown helminthiasis was more prevalent in adult pigeon than in squab, but analysis with Chi-square test shown no significant association between helminthiasis infection and age of the pigeons (P>0.05). Quantitative exam with McMaster method shown degree of infection of single Ascaridia infection in adult pigeons is 340 EPG while in Capillaria sp. is 287.5 EPG and 150 EPG in Heterakis. All of them are considered mild infection. Thus, proper loft and feed hygene method should be informed to prevent more transmission.